Synsedimentary faults and amalgamated unconformities : Insights from 3D-seismic and core analysis of the Lower Triassic Middle Buntsandstein, Ems Trough, north-western Germany. - Radies, Dirk; Stollhofen, Harald; Hollmann, Gregor; Kukla, Peter (International Journal of Earth Sciences, 2005)
The Late Permian/Early Triassic succession of the Central European Basin (CEB) was repeatedly affected by the tectonic pulses associated with the earliest phases of Tethyan and Arctic-North Atlantic rifting. Effects of the differential tectonic subsidence are particularly well recorded by unconformities, which form widespread sequence boundaries. Such unconformities are most obvious in areas occupied by fault-controlled intra-basinal highs (swells). In that areas, stratigraphic loss may comprise entire Lower and Middle Buntsandstein formations and in places remnant Middle Buntsandstein successions directly rest on Permian strata. Analysis of 3D-seismic data and well logs combined with high-resolution sedimentological logging of drillcores at the western margin of the Ems Trough (NW Germany) reveals details of synsedimentary tectonic control on sequence development. Early Triassic extensional faulting of basement blocks provided stepwise addition of accommodation space for continental sequences by growth faulting along north-south oriented fault zones blocks on the flanks of the East Netherlands High. This process is most evident during the development of the Hardegsen Unconformity, which is characterised by an amalgamation of succeeding unconformity surfaces in areas of structurally controlled intrabasinal highs. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LG.synsed
Keywords: Buntsandstein; Continental sequences; Early Triassic; Synsedimentary tectonics; Unconformities